Pengaruh Motivasi Intrinsik dan Kesadaran Metakognitif terhadap Prestasi Akademik Siswa - Tuty Alawiyah; Encep Supriatna; Wiwin Yuliani (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2019)
This study aims to examine the impact of instrinsic motivation and metacognitive awareness on students academic achievement. The study first tries to investigate whether there are any correlation between intrinsic motivation and students academic achievement and also the correlation between metacognitive awareness and academic achievement. The study then goes to search whether intrinsic motivation and metacognitive awareness when they are combined together have impact on student’s academic achievement. The sample of this study consist of 387 Senior High School students. The data collection is conducted with the use of Intrinsic Motivation Inventory (IMI), Metacognitive Awareness Inventory (MAI) and the students’ grades. As a result, it was found that intrinsic motivation has significant impact on the student’s academic achievement, meanwhile metacognitive awareness has no impact on students’ academic achievement. But, intrinsic motivation and metacognitive awareness when they are combined together gave 4% contribution to academic achievement.